Diurnal and Seasonal Variations of Photosynthetic Energy Conversion Efficiency of Field Grown Wheat - Song, Qingfeng; Van Rie, Jeroen; Den Boer, Bart; Galle, Alexander; Zhao, Honglong; Chang, Tiangen; He, Zhonghu; Zhu, Xin-Guang (Frontiers in Plant Science, 2022)
Improving canopy photosynthetic light use efficiency (LUE) and energy conversion efficiency (ec) is a major option to increase crop yield potential. However, so far, the diurnal and seasonal variation of canopy LUE and ec are largely unknown due to lack of efficient method to estimate ec in a high temporal resolution. Here we quantified the dynamic changes of crop canopy LUE and ec during a day and a growing season with canopy gas exchange method. A response curve of whole plant CO2 flux to incident PAR was further used to calculate ec and LUE at a high temporal resolution. Results show that the LUE of two wheat cultivars with different canopy architectures at five stages varies between 0.01 to about 0.05 mol CO2 mol-1 photon, with the LUE being higher under medium PAR. Throughout the growing season, the ec varies from 0.5% to 3.7% (11%~80% of the maximal ec for C3 plants) with incident PAR identified as a major factor controlling variation of ec. The estimated average ec from tillering to grain filling stages was about 2.17%, i.e. 47.2% of the theoretical maximal. The estimated season-averaged radiation use efficiency (RUE) was 1.5~1.7 g MJ-1, which was similar to the estimated RUE based on biomass harvesting. The large variations of LUE and ec imply great opportunity to improve canopy photosynthesis for greater wheat biomass and yield potential.